The role of point-of-care ultrasound in detecting an occult pediatric elbow fracture missed on plain film: A case report - India Rogers-Shepp; Andrew Parambath, MD/MBA/M.Ed; Timothy J. Batchelor, MD (Radiology Case Reports)
It has been proposed that sonography be utilized as an early imaging modality of choice when evaluating a pediatric elbow injury. We present a case where traditional plain film radiography was preferentially employed and failed to find diagnostic evidence of a fracture. When point-of-care ultrasound (POCUS) was employed to further evaluate for an occult fracture, it revealed indirect signs of injury requiring acute treatment and further orthopedic evaluation. Had POCUS been performed first, as proposed in some literature, its high sensitivity and ability to evaluate indirect signs of fracture may have spared this patient ionizing radiation exposure and longer wait times. This case shows the potential of POCUS to be used as a first-line imaging tool when evaluating pediatric elbow injuries. We advocate for more research to investigate this possibility.